Transplanting international courts : the law and politics of the Andean Tribunal of Justice - Alter, Karen J.; Helfer, Laurence R. (Oxford, United Kingdom : Oxford University Press, 2017)
"[This book offers a] systematic investigation of the most active and successful transplant of the European Court of Justice. The Andean Tribunal is effective by any plausible definition of the term, but only in the domain of intellectual property law. [The authors] explain how the Andean Tribunal established its legal authority within and beyond this intellectual property island, and how Andean judges have navigated moments of both transnational political consensus and political contestation over the goals and objectives of regional economic integration. By letting member states set the pace and scope of Andean integration, by condemning unequivocal violations of Andean rules, and by allowing for the coexistence of national legislation and supranational authority, the Tribunal has retained its fidelity to Andean law while building relationships with nationally-based administrative agencies, lawyers, and judges. Yet the Tribunals circumspect and formalist approach means that, unlike in Europe, community law is not an engine of integration. The Tribunals strategy has also limited its influence within the Andean legal system ... [The authors] argue that the European Court of Justice benefitted in underappreciated ways from the support of transnational jurist advocacy movements that are absent or poorly organized in the Andes and elsewhere in the world. The Andean Tribunals longevity despite these and other challenges offers guidance for international courts in other developing country contexts. Moreover, given that the Andean Community has weathered member state withdrawals and threats of exit, major economic and political crises, and the retrenchment of core policies such as the common external tariff, the Andean experience offers timely and important lessons for European international courts."--
Lessons from the Andean Tribunal of Justice : thirty years as a legal transplant -- Transplanting the European Court of Justice to the Andes / t
Includes bibliographical references (pages 291-302) and index.
Keywords: Tribunal de Justicia del Acuerdo de Cartagena; Tribunal de Justicia del Acuerdo de Cartagena; Cartagena Agreement -- (1969); Cartagena Agreement (1969); Courts -- Andes Region; Courts; Politics and government; Andes Region -- Politics and government; Andes Region